2020
DOI: 10.1002/ppul.25193
|View full text |Cite
|
Sign up to set email alerts
|

Ultrashort inspiratory times homogenize ventilation distribution in an inhomogeneous two‐compartment model of the neonatal lung

Abstract: Background: Inhomogeneous lung ventilation and pulmonary air leaks are common adverse effects of mechanical ventilation in preterm infants suffering from respiratory distress syndrome. We hypothesized that shortening of inspiratory times can improve the homogeneity of lung aeration. We assumed that ultrashort inspiratory times lead to a full build-up of pressure in regions with low compliance while maintaining incomplete filling of regions with high compliance. Methods: We connected a two-compartment model of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
(36 reference statements)
0
1
0
Order By: Relevance
“…Several other papers focusing on different aspects of pulmonary physiology were published in 2021 and 2022. Baumgartner et al 56 studied the effect of ultrashort inspiratory times (0.1‐0.2 second)s) on ventilation inhomogeneity in a two compartment neonatal lung model of differential ventilation consisting of a low compliance and high compliance lung unit. They found that shorter inspiratory times (e.g., 0.2 s) resulted in more homogeneous ventilation, suggesting that using such inspiratory times in conditions such as bronchopulmonary dysplasia may be beneficial.…”
Section: Introductionmentioning
confidence: 99%
“…Several other papers focusing on different aspects of pulmonary physiology were published in 2021 and 2022. Baumgartner et al 56 studied the effect of ultrashort inspiratory times (0.1‐0.2 second)s) on ventilation inhomogeneity in a two compartment neonatal lung model of differential ventilation consisting of a low compliance and high compliance lung unit. They found that shorter inspiratory times (e.g., 0.2 s) resulted in more homogeneous ventilation, suggesting that using such inspiratory times in conditions such as bronchopulmonary dysplasia may be beneficial.…”
Section: Introductionmentioning
confidence: 99%